Enhancing the physicochemical and functional properties of gelatin/ graphene oxide/cinnamon bark oil nanocomposite packaging films using ferulic acid - Z.A., Maryam Adilah; F., Han Lyn; B., Nabilah; B., Jamilah; C., Gun Hean; Z. A., Nur Hanani (Elsevier, 2022)
Protein such as fish gelatin (FG) is widely used as a raw material to develop biodegradable packaging. However, its mechanical and water vapour barrier properties are still inferior as compared to synthetic polymers. Thus, in this research, a reinforcing nanofiller which is graphene oxide (GO, 2% w/w based on FG) and a crosslinking process using ferulic acid (FA) were incorporated to produce gelatin-graphene oxide/ferulic acid (gel-GO/FA) films with enhanced properties. Different concentrations of FA (0%, 0.5%, 1.0%, 2.0%, 3.0%, and 4.0% w/w) were used and the resulting films were analyzed. Cinnamon bark oil (CEO, 5% w/w based on FG) was incorporated to enhance the antioxidant activities of the films. The incorporation of FA resulted in a denser film microstructure and increased tortuosity, as shown by scanning electron microscopy (SEM) as well as the decreased (p < 0.05) water vapour permeability of the films. The antioxidant activities of the films improved significantly (p < 0.05) with FA concentration, with the highest values of DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging activity, ABTS (2,2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid) scavenging activity, and total phenolic content of 97.41%, 98.67%, and 79.50 mg GAE/ g, respectively. In this study, the optimal concentration of the FA is 1% as the films showed the highest (p < 0.05) Young’s modulus and tensile strength. In addition, 1% FA was sufficient to result in a significant (p < 0.05) decrease of the ultraviolet (UV) light transmittance (wavelength= 200. 280, and 400 nm) and opacity. This research reveals that crosslinking gel-GO films with FA can improve the mechanical, water vapour and light barrier, thermal stability, as well as functional properties, potentially broadening their applications as food packaging.